Organ Impairment—Drug–Drug Interaction Database: A Tool for Evaluating the Impact of Renal or Hepatic Impairment and Pharmacologic Inhibition on the Systemic Exposure of Drugs. (14th July 2015) - Yeung, CK; Yoshida, K; Kusama, M; Zhang, H; Ragueneau‐Majlessi, I; Argon, S; Li, L; Chang, P; Le, CD; Zhao, P; Zhang, L; Sugiyama, Y; et al.
<x xml:space="preserve">Abstract</x> The organ impairment and drug–drug interaction (OI‐DDI) database is the first rigorously assembled database of pharmacokinetic drug exposure data from publicly available renal and hepatic impairment studies presented together with the maximum change in drug exposure from drug interaction inhibition studies. The database was used to conduct a systematic comparison of the effect of renal/hepatic impairment and pharmacologic inhibition on drug exposure. Additional applications are feasible with the public availability of this database.